Среди монет: Книга для учащихся средних и старших классов / Г. М. Семар - Семар Геннадий Мигранович (Просвещение, 1990)
Экземпляры: (20170321) / Инвентарный номер: 26762 / Цена: 0.30 / Сис.шифр: 63.2 / Авт.знак: С 30 / ББК: 63.2